States of Obligation and the Elusive Rural Citizen - Gaudin, Corinne (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2016)
This essay opens the discussion of Yanni Kotsonis’ States of Obligation by exploring what implications the book’s arguments about taxation and citizenship have for our understanding of fraught state-peasant relations in the late Imperial and Soviet periods. It argues that in addition to the technocratic, philosophical, and bureaucratic continuities that shaped the Russian/Soviet variant of European modernity, one could add a cultural and temporal conception of citizenship that rendered the peasant an ever elusive citizen.